Solution of Second-Order IVP and BVP of Matrix Differential Models Using Matrix DTM - Reza Abazari; Adem Kılıcman (Abstract and Applied Analysis)
We introduce a matrix form of differential transformation method (DTM) and apply for nonlinear second-order initial value problems (IVPs) and boundary value problems (BVPs) of matrix models which are given by 𝐮(𝑡)=𝑓(𝑡,𝐮(𝑡),𝐮(𝑡)) and subject to initial conditions 𝐮(𝑎)=𝐮0,𝐮(𝑎)=𝐮1 and boundary conditions 𝐮(𝑎)=𝐮0,𝐮(𝑏)=𝐮1, where 𝐮0,𝐮1∈𝑅𝑟×𝑞. Also the convergence of present method is established. Several illustrative examples are given to demonstrate the effectiveness of the present method.